Gambaran kualitas hidup remaja SMA dengan berat badan berlebih di Manado pada Pandemi COVID-19 - Jalaham, Dinda Novitri; Ottay, Ronald I.; Palandeng, Henry M. F. (UNIVERSITAS SAM RATULANGI, 2020)
Background: Adolescence is the period of transitions between childhood and adulthood, in this period there are many changes that cover various aspects such as physical, hormonal, psychological, and even social development. The prevalence of overweight and obesity among children and adolescents aged 5-19 has risen from just 4% in 1975 to over 18% in 2016. Overweight and obese have a high risk of non-communicable diseases that can affect someoneâ€™s quality of life. The main purpose of this research is to find out the outline ofÂ overweight adolescentsâ€™ quality of life. Methods: This was a descriptive cross-sectional study on 44 adolescents who are overweight from high schools in Manado city. Results: The results of this study indicate that students who are overweight have a moderate quality of life in the physical health psychological, social, and environmental domains.Conclusion: The majority of respondents in this study had a moderate quality of life.Keywords: Adolescent, overweight, quality of life